Histomorphometric analysis of osteocyte lacunae in human and pig: exploring its potential for species discrimination - Cummaudo, Marco; Cappella, Annalisa; Giacomini, Francesca; Raffone, Caterina; Márquez-Grant, Nicholas (Springer, 2019)
In recent years, several studies have focused on species discrimination of bone fragments by histological analysis. According to literature, the most consistent distinguishing features are Haversian canal and Haversian system areas. Nonetheless, there is a consistent overlap between human and non-human secondary osteon dimensions. One of the features that have never been analyzed for the purpose of species discrimination is the osteocyte lacuna, a small oblong cavity in which the osteocyte is locked in. The aim of this study is to verify whether there are significant quantitative differences between human and pig lacunae within secondary osteons with similar areas. Study sample comprises the midshaft of long bones (humerus, radius, ulna, femur, tibia, and fibula) of a medieval human adult and a juvenile pig. Sixty-eight secondary osteons with similar areas have been selected for each species and a total of 1224 osteocyte lacunae have been measured. For each osteon, the total number of lacunae was counted, and the following measurements were taken: minimum and maximum diameter, area, perimeter, and circularity of nine lacunae divided between inner, intermediate, and outer lacunae. Statistical analysis showed minimal differences between human and pig in the number of lacunae per osteons and in the minimum diameter (P > 0.05). On the contrary, a significant difference (P < 0.001) has been observed in the maximum diameter, perimeter, area, and circularity. Although there is the need for further research on different species and larger sample, these results highlighted the potential for the use of osteocyte lacunae as an additional parameter for species discrimination. Concerning the difference between the dimensions of osteocyte lacunae based on their position within the osteon (inner, intermediate, and outer lacunae), results showed that their size decreases from the cement line towards the Haversian canal both in human and pig.
Keywords: Forensic anthropology; Bone histology; Bone lacunae; Bioarchaeology; Human vs non-human; Sus scrofa.